The analgesic effect and ATP release at acupuncture points in response to acupuncture with different parameters on arthritis rats - Jie LIN; Kai-yu CUI; Yu-jia LI; Wei-min ZUO; Jing-wen XU; Xue-yong SHEN; Guang-hong DING; Xiao-long TANG; Li-na WANG (World Journal of Acupuncture - Moxibustion)
Objective: Previous studies indicated a close correlation between manual acupuncture (MA) analgesia and the mobilization of extracellular adenosine triphosphate (ATP) at the acupoints. This study attempted to investigate whether this relationship is altered with the manipulation patterns of MA. Additionally, we further testified whether these two events parallelly varied with different frequencies of electroacupuncture (EA). Methods: Male SD rats were randomly divided into four groups: blank group, model group, MA group, and EA group. MA group was further divided into four sub-groups: standard MA, sham MA, lifting-thrusting MA, and shallow MA. Similarly, EA group was categorized based on current frequency into 2 Hz, 2–100 Hz, 100 Hz, and ARL67156+100 Hz sub-groups. For the behavioral tests, each group comprised 4–8 rats; for extracellular ATP assessment, each group consisted of 3–6 rats. Complete Freund’s adjuvant (CFA) was injected into the left ankle joint cavity to create an acute adjuvant arthritis (AA) model. A 20-minute session of either MA at left Zusanli (ST36) or EA at bilateral ST36 was administered on AA rats. Thermal hyperalgesia of the hind paw was determined. Extracellular ATP in the interstitial space at ST36 (inters. ATP) was extracted using microdialysis and quantified via a luciferase-luciferin assay. Results: Modeling induced tenderness at ST36 (P < 0.001) and higher ATP mobilization (P < 0.05) in response to MA. Both standard MA (P < 0.001) and lifting-thrusting manipulation (P < 0.001) exhibited a remarkable analgesic effect, which was not observed with sham MA, deep insertion plus retention. Verum MA (P < 0.001) rather than sham intervention, significantly elevated inters. ATP levels. Notably, shallow MA, penetrating the skin layer and needling with twirling-rotating, demonstrated analgesia and increasing inters. ATP level (P < 0.05). Regarding EA, treatments at frequencies of 2 Hz (P < 0.01), 2–100 Hz (P < 0.05), and 100 Hz (P < 0.05) significantly alleviated pain. Only the 2–100 Hz (P < 0.05) and 100 Hz (P < 0.01) interventions, particularly in the latter, potentiated ATP mobilization. Preventing ATP hydrolysis dampened the analgesic effects of the standard MA and 100 Hz EA. Conclusion: There is a general correlation between ATP mobilization at the acupoint and the analgesic effect of MA and EA. However, the underlying mechanisms related to shallow MA and 2 Hz EA remain to be elucidated.